Strong Sustainability and Ocean Justice: Fostering Coastal Community Well-Being in Indonesia - Tarigan, Muhammad Insan; Ferdinanto, Tonny (Universitas Brawijaya, 2024)
Poverty and environmental issues are interconnected and entangled in complex human-environment relationships. Poor people often degrade the environment to meet present needs at the expense of their future benefits. Conversely, environmental degradation exacerbates poverty by deteriorating livelihoods, income, and health. This nexus is prevalent in coastal communities’ interactions with coastal and ocean ecosystems. The severe environmental degradation of coastal habitats and oceans endangers coastal communities whose livelihoods depend on marine ecosystem services. Millions of people depend directly on marine resources as their main source of food and income. Indonesia has the second-largest coastline in the world, stretching approximately 81,000 kilometres. Unfortunately, the threat to the sustainability of marine biodiversity is getting more complex. Strengthening the capacity of coastal communities as key actors in managing and protecting coastal sustainability can ensure their well-being. This article identifies and proposes a robust regulatory framework for ocean justice in Indonesia’s coastal regions. A conceptual approach is employed to achieve this goal, with a review of pertinent legal literature and documents. In addition, the critical legal studies method will be utilised to identify potential areas for improvement. It can be argued that Indonesia has yet to achieve the robust sustainability level currently being sought. The concept of strong sustainability is grounded in two fundamental moral principles: environmental ethics and distributive justice. The legal apparatus governing ocean management must be modified to address evolving governance challenges. Although robust sustainability is not the sole determining factor of community well-being, the institutionalisation of ocean justice has the potential to facilitate the actualisation of community well-being in Indonesia's coastal regions.